Sustainable dimension pillars adaptation in neighborhood assessment criteria of community planning & design - Yaman, Rostam; Thadaniti, Suwattana; Suntornvongsagul, Kallaya; Adnan, Hamimah; Ahmad, Noraini (Universiti Teknologi Malaysia (UTM), 2017)
This paper presents the study of sustainable dimension pillars (SDP) on neighborhood assessment sub-criteria of community planning & design. The problem of the study is to find out whether the townships assessment tools fully address sustainability or it might be ‘green but not sufficient’ to be sustainable. The aim of the study is to evaluate the adaptation and balance of SPD in Community, Planning, and Design (CPD), which is one of the core-criteria of GBI Township/Neighborhood Assessment Criteria. The objective is to identify and evaluate the adaptation of SPD indicators balance towards sustainable urban development in Malaysia. The expert interview and questionnaires survey approach is used in this study in order to gather experts’ opinion regarding the SPD indicators in the CPD sub-criteria. The significant contribution of the research is the findings will be used as references/guides for future review and refinement GBI Township/Neighborhood Assessment Criteria.